2014
DOI: 10.3109/09513590.2014.971236
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the presence and severity of menopausal symptoms among postmenopausal women screened for the metabolic syndrome

Abstract: In this postmenopausal sample, severity of menopausal symptoms correlated to abdominal obesity, mood and other personal aspects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
0
12
0
1
Order By: Relevance
“…Chou et al [16] also reported sleep problems as the fourth most common symptom. Depressive mood was added to these symptoms in some studies [17][18][19]. Another study reported that vasomotor symptoms such as hot flashes are the most common in the menopausal period [20].…”
Section: Discussionmentioning
confidence: 99%
“…Chou et al [16] also reported sleep problems as the fourth most common symptom. Depressive mood was added to these symptoms in some studies [17][18][19]. Another study reported that vasomotor symptoms such as hot flashes are the most common in the menopausal period [20].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this is true as menopausal estrogens are synthesized by aromatization of androgens in the fat tissue and this phenomena explains differences observed in studies addressing the duration and the intensity of symptoms after the menopause onset [23,24]. In this sense, although the primary aim of the original cohort was to screen for the METS, prevalence of the METS or of its components did not vary in accordance to the genotypes of the studied CYP polymorphism, nor did menopausal symptom intensity vary according to genotype after stratifying for the presence of the METS or its components; despite the fact that the same cohort presented more severe menopausal symptoms related to obesity [12].…”
Section: Discussionmentioning
confidence: 96%
“…We previously reported data of a cross-sectional study carried out from December 2011 to June 2012 at the Institute of Biomedicine of the Medical Faculty of the Universidad Católica de Santiago de Guayaquil, Guayaquil, Ecuador, regarding menopausal and depressive symptoms among women screened for the metabolic syndrome (METS) [12]. Through newspaper advertisement, a total of 204 natural postmenopausal women (40-65 years) were recruited who were not on menopausal hormone therapy (MHT), phytoestrogens or drugs intended to decrease lipid levels.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Accordingly, there have been numerous efforts to develop compounds capable of modulating ER-mediated signaling pathways, and several selective estrogen receptor modulators (SERMs) and aromatase inhibitors have been approved. To date, the major clinical applications of SERMs are in the treatment of ER-positive breast cancer and the prevention and treatment of postmenopausal symptoms caused by the low levels of estrogens that accompany osteoporosis (1)(2)(3). In addition, recent studies suggest the possible use of SERMs as neuroprotective agents (4,5).…”
Section: Introductionmentioning
confidence: 99%